OncomiR addiction is generated by a miR-155 feedback loop in Theileria-transformed leukocytes. - Justine Marsolier; Sandra Pineau; Souhila Medjkane; Martine Perichon; Qinyan Yin; Erik Flemington; Matthew D Weitzman; Jonathan B Weitzman (PLoS Pathogens)
The intracellular parasite Theileria is the only eukaryote known to transform its mammalian host cells. We investigated the host mechanisms involved in parasite-induced transformation phenotypes. Tumour progression is a multistep process, yet 'oncogene addiction' implies that cancer cell growth and survival can be impaired by inactivating a single gene, offering a rationale for targeted molecular therapies. Furthermore, feedback loops often act as key regulatory hubs in tumorigenesis. We searched for microRNAs involved in addiction to regulatory loops in leukocytes infected with Theileria parasites. We show that Theileria transformation involves induction of the host bovine oncomiR miR-155, via the c-Jun transcription factor and AP-1 activity. We identified a novel miR-155 target, DET1, an evolutionarily-conserved factor involved in c-Jun ubiquitination. We show that miR-155 expression led to repression of DET1 protein, causing stabilization of c-Jun and driving the promoter activity of the BIC transcript containing miR-155. This positive feedback loop is critical to maintain the growth and survival of Theileria-infected leukocytes; transformation is reversed by inhibiting AP-1 activity or miR-155 expression. This is the first demonstration that Theileria parasites induce the expression of host non-coding RNAs and highlights the importance of a novel feedback loop in maintaining the proliferative phenotypes induced upon parasite infection. Hence, parasite infection drives epigenetic rewiring of the regulatory circuitry of host leukocytes, placing miR-155 at the crossroads between infection, regulatory circuits and transformation.